2016
DOI: 10.17222/mit.2015.253
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gas atmosphere on the non-metallic inclusions in laser-welded trip steel with Al and Si additions

Abstract: The present study aims to characterize the weldability of a multiphase, automotive steel containing Al and Si additions from the point of view of its tendency to form non-metallic inclusions. Laser welding tests of 2-mm-thick sheets were performed using the keyhole-welding mode and a solid-state laser. The tests were carried out in air and with the use of an argon atmosphere. The distribution, type and chemical composition of the non-metallic inclusions formed in the base metal and fusion zones were analysed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…The precipitation hardening was mainly triggered by dispersive precipitates of several nanometres in size, precipitated in the steel (in ferrite) during cooling ( Figure 2) [28][29][30][31][32]. Particles sized above twenty nanometres did not significantly contribute to precipitation hardening, yet they restrained the recrystallised austenite grain growth, favouring the formation of the fine-grained structure [28,[33][34][35][36][37]. The recrystallised austenite grain growth in the test steel was primarily restrained by precipitates of globular (Nb,Ti)C carbides of approximately 10 nm in diameter and characterised by niobium predominance [38], precipitates of (Ti,Nb)C carbides of approximately 20 nm in size, and (Ti,Nb)(C,N) precipitates of approximately 50 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…The precipitation hardening was mainly triggered by dispersive precipitates of several nanometres in size, precipitated in the steel (in ferrite) during cooling ( Figure 2) [28][29][30][31][32]. Particles sized above twenty nanometres did not significantly contribute to precipitation hardening, yet they restrained the recrystallised austenite grain growth, favouring the formation of the fine-grained structure [28,[33][34][35][36][37]. The recrystallised austenite grain growth in the test steel was primarily restrained by precipitates of globular (Nb,Ti)C carbides of approximately 10 nm in diameter and characterised by niobium predominance [38], precipitates of (Ti,Nb)C carbides of approximately 20 nm in size, and (Ti,Nb)(C,N) precipitates of approximately 50 nm in size.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3]. One of the most interesting and evolving groups of advanced steels for the automotive industry is the multiphase transformation-induced plasticity (TRIP)-aided steels consisting of ferrite, bainite, and retained austenite [4][5][6]. These steels utilize different strengthening mechanisms to improve their strength level, but the most important is the strain-induced transformation of retained austenite into martensite [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of non-metallic inclusions when welding steel TRIP in the atmosphere of air and argon was explained by Grajcar et al [17]. They reported that the use of argon as the shielding gas during laser welding led to the slight reduction of non-metallic inclusions.…”
Section: Microstructure Investigationsmentioning
confidence: 99%
“…They have also tested the effect of welding parameters on the presence of non-metallic inclusions in the fusion zone of welded joints [17]. Advanced High Strength Steels, particularly those characterised by significantly high strength tend to be problematic during welding.…”
Section: Introductionmentioning
confidence: 99%